2015
DOI: 10.1177/1420326x15587564
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of indoor environment quality in LEED-certified healthcare settings

Abstract: A combination of quantitative and qualitative approaches was used to evaluate the effectiveness of LEED-certified healthcare settings from the perspectives of both staff and facility managers. This study surveyed 164 staff members in two healthcare settings in a case study to compare LEED and non-LEED-certified healthcare facilities and surveyed 146 staff in six LEED-certified healthcare settings for the main study. Telephone interviews with six facility managers were used to verify the survey results and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
0
12
0
2
Order By: Relevance
“…Evaluate Occupants To evaluate occupants' comfort, satisfaction, well-being, or health [27][28][29][30][31]; investigate the factors that affect their satisfaction [32][33][34]; understand their opinions or experiences of a space [35][36][37][38]; assess their productivity [39,40]; understand occupant behavior [41][42][43][44][45]; assess occupant opinions of green building rating tools [46,47]; or evaluate the sociality of occupants [48].…”
Section: Figure 4 Number Of Projects and Number Of Buildings Per Typementioning
confidence: 99%
“…Evaluate Occupants To evaluate occupants' comfort, satisfaction, well-being, or health [27][28][29][30][31]; investigate the factors that affect their satisfaction [32][33][34]; understand their opinions or experiences of a space [35][36][37][38]; assess their productivity [39,40]; understand occupant behavior [41][42][43][44][45]; assess occupant opinions of green building rating tools [46,47]; or evaluate the sociality of occupants [48].…”
Section: Figure 4 Number Of Projects and Number Of Buildings Per Typementioning
confidence: 99%
“…4 Green buildings have become popular, and many studies have been conducted to evaluate the IEQ of green buildings, such as LEED-certified buildings. Previous studies 59 have demonstrated that LEED-certified buildings are superior to non-LEED facilities in building performance factors. A study documented in the Center for the Built Environment database 10 analysed 15 LEED certified green buildings and concluded that acoustics, thermal quality, lighting, cleanliness and space could score positive satisfaction ratings with occupants.…”
Section: Introductionmentioning
confidence: 98%
“…14 Through comparing two healthcare facilities on opposite sides of the street that belong to one healthcare system, it is clear that the LEED-certified healthcare setting is better than the non-LEED one in cleanliness, thermal comfort, safety, noise comfort, lighting comfort, overall comfort, perceived productivity, image presented to visitors, meeting staff needs and efficiency of space use. 9 By comparing a LEED-certified renovation of a pediatric healthcare facility with its previous, conventional counterpart, statistically significant improvements were found in productivity, staff satisfaction and quality of care. 15…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that most studies on building IEQ have considered thermal comfort, indoor air quality (IAQ), lighting, and acoustics as the main parameters to determine the indoor comfort level [3][4][5][6][7]. Numerous studies have integrated physical measurements and subjective surveys on the above four aspects of IEQ to determine the optimal design of healthcare facilities and better built environments [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%